2015
DOI: 10.4103/0019-5545.148532
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunctions in schizophrenia: Professionals and patients perspectives

Abstract: Background:Sexual dysfunction (SD) is not commonly reported by persons with schizophrenia unless an enquiry is made by a doctor or staff during routine clinical visits.Materials and Methods:A cross-sectional study was carried out to determine reporting of drug-induced sexual side-effects and the attitude of the treating team in clarifying or detecting this issue.Results:A vast majority of professionals (73.2%) did not enquire about SDs in routine clinical setting and admitted that they lack expertise based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Again, cross-cultural factors are probably important, as an investigation in India, using the PRSexDQ-SALSEX questionnaire, found that most patients (91.7%) reported good to fair tolerance of any sexual side effects 28 .…”
Section: Influence Of Treatment Of Psychosis On Sexualitymentioning
confidence: 99%
“…Again, cross-cultural factors are probably important, as an investigation in India, using the PRSexDQ-SALSEX questionnaire, found that most patients (91.7%) reported good to fair tolerance of any sexual side effects 28 .…”
Section: Influence Of Treatment Of Psychosis On Sexualitymentioning
confidence: 99%
“…Our study highlights the need for checking sexual dysfunction in this patients. 16 On one hand schizophrenia is associated with sexual dysfunction while on the other medicines used for its treatment i.e. antipsychotics are also well known to cause sexual dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric disease is among the most important risk factors for women's sexual dysfunction [26][27][28][29]. Women with schizophrenia and schizophrenia spectrum disorders reported a very high burden of sexual dysfunction, with 60-80% of women being affected [30][31][32][33][34][35]. In addition, antipsychotic medications, symptoms of psychosis, institutionalization and societal stigma are all likely contributory factors [36].…”
Section: Introductionmentioning
confidence: 99%